O-linked N-acetylglucosaminylation of Sp1 inhibits the human immunodeficiency virus type 1 promoter - Jochmann, Ramona; Thurau, Mathias; Jung, Susan; Hofmann, Christian; Naschberger, Elisabeth; Kremmer, Elisabeth; Harrer, Thomas; Miller, Matthew; Schaft, Niels; Stürzl, Michael (Journal of Virology, 2009)
Human immunodeficiency virus type 1 (HIV-1) gene expression and replication are regulated by the promoter/enhancer located in the U3 region of the proviral 5′ long terminal repeat (LTR). The binding of cellular transcription factors to specific regulatory sites in the 5′ LTR is a key event in the replication cycle of HIV-1. Since transcriptional activity is regulated by the posttranslational modification of transcription factors with the monosaccharide O-linked N-acetyl-D-glucosamine (O-GlcNAc), we evaluated whether increased O-GlcNAcylation affects HIV-1 transcription. In the present study we demonstrate that treatment of HIV-1-infected lymphocytes with the O-GlcNAcylation-enhancing agent glucosamine (GlcN) repressed viral transcription in a dose-dependent manner. Overexpression of O-GlcNAc transferase (OGT), the sole known enzyme catalyzing the addition of O-GlcNAc to proteins, specifically inhibited the activity of the HIV-1 LTR promoter in different T-cell lines and in primary CD4+ T lymphocytes. Inhibition of HIV-1 LTR activity in infected T cells was most efficient (>95%) when OGT was recombinantly overexpressed prior to infection. O-GlcNAcylation of the transcription factor Sp1 and the presence of Sp1-binding sites in the LTR were found to be crucial for this inhibitory effect. From this study, we conclude that O-GlcNAcylation of Sp1 inhibits the activity of the HIV-1 LTR promoter. Modulation of Sp1 O-GlcNAcylation may play a role in the regulation of HIV-1 latency and activation and links viral replication to the glucose metabolism of the host cell. Hence, the establishment of a metabolic treatment might supplement the repertoire of antiretroviral therapies against AIDS. Copyright © 2009, American Society for Microbiology. All Rights Reserved.
Created from Fastlane, Scopus look-up